2012
DOI: 10.1258/phleb.2011.011063
|View full text |Cite
|
Sign up to set email alerts
|

Saphenopopliteal ligation and stripping of small saphenous vein: does extended stripping provide better results?

Abstract: SPL with or without stripping is an effective procedure improving clinical severity and QoL in the short term. Early outcomes favour SPL with extended stripping to offer greater improvement in disease-specific QoL, venous severity and cosmesis. With this small sample, there is no evidence of increased complications following stripping, or increased short-term recurrence without it. Greater numbers and follow-up are required to make firm conclusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 31 publications
1
5
1
4
Order By: Relevance
“…Tong and Royle [ 4 ] previously reported that recurrence was attributed to an intact incompetent SPJ in 28% of 70 cases of recurrent varicose veins following SSV surgery. However, other studies have shown that flush ligation of the SPJ by formal exploration of the popliteal fossa did not appear to affect outcomes [ 7 ] and was associated with major complications [ 11 , 12 ]. Rashid et al [ 12 ] reported a low technical success rate (59%) after formal SPJ dissection, with three major complications occurring, including DVT and tearing of the popliteal vein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tong and Royle [ 4 ] previously reported that recurrence was attributed to an intact incompetent SPJ in 28% of 70 cases of recurrent varicose veins following SSV surgery. However, other studies have shown that flush ligation of the SPJ by formal exploration of the popliteal fossa did not appear to affect outcomes [ 7 ] and was associated with major complications [ 11 , 12 ]. Rashid et al [ 12 ] reported a low technical success rate (59%) after formal SPJ dissection, with three major complications occurring, including DVT and tearing of the popliteal vein.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the 2-cm angled segment was left untreated for two reasons: (1) preservation of the gastrocnemius veins that enter into this segment, and (2) because the tibial nerve enters into close proximity with the SSV at this deeper level. In the literature, clinical recurrence of SSV varicose veins after surgical treatment has been reported to range from 8.6% to 30% [ 7 , 11 , 13 , 14 ]. The most common cause of recurrence after surgical treatment of the SSV is neovascularization [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Die hohe Quote nachweisbarer Parvastümpfe ist ein Beleg dafür, dass keine korrekte saphenopopliteale Ligatur vorgenommen wurde. Von der einfachen subfaszialen Parvaligatur [5,6] bis zur saphenopoplitealen Ligatur [27,31,34] ist alles vertreten. In der Arbeit von Allegra et al [1] mit 30 % Kros-senrezidiven nach 5 Jahren ist überhaupt keine OP-Technik angegeben.…”
Section: Kohortenstudie Zur Parvakrossektomieunclassified
“…Die sehr umfangreiche Arbeit von Brittenden et al basiert auf den Ergebnissen der in Großbritannien und Nordirland durchgeführten Untersuchungen. Diesbezüglich darf auf die Problematik der oben aufgelisteten Untersuchungen von Winterborn et al [54], Rashid et al [40] und Samuel et al [44] verwiesen werden. Eine korrekte Parvacrossektomie wird nicht oder zumindest sehr selten (10 % in der Analyse von Winterborn et al durchgeführt).…”
Section: Ergebnisse Der Endoluminalen Behandlungunclassified